Biodegradation of p-Hydroxybenzoate by Microorganisms in Sediment-slurry under Aerobic Conditions - นิ่มรัตน์ สุบัณฑิต; ทรัพย์วิลาวรรณ วีรญา; สุพรรณพันธุ์ พีรพัฒน์; วุฒิพันธุ์ชัย วีรพงศ์ (KKU Science Journal, 2014)
The biodegradation of p-hydroxybenzoate with microorganisms in sediment-slurry from rice paddy under aerobic conditions was investigated. In active experiment, 0.1 mM of p-hydroxybenzoate which was applied in the first and the second time were biodegraded within 3 and 2 days, respectively. While 0.3 mM of p-hydroxybenzoate was biodegraded within 5 days. In the first time, which added with 0.1 mM was found 1.0 ml of gas produced and decreased all along the experiment. The bacteria isolated from sediment-slurry in this present active treatment were identified as belong to Bacillus sp. Microorganisms in sediment-slurry from rice paddy under aerobic conditions were also able to transform nitrate to nitrite.